Opinion of Indian undergraduate clinical students regarding the five-year BDS curriculum - Amith Holenarsipur Vasanthakumar; Audrey Madonna D'Cruz (Wolters Kluwer Medknow Publications, 2014)
Background: The Dental Council of India, in 2010, had changed the curriculum from the four years and one-year internship course to a five-year course without internship. Later in 2011, the Dental Council of India gave the liberty to individual universities to decide upon a comprehensive five-year course without internship or a BDS course of four years and one-year internship. Aim: To gauge the overall attitude of students toward revision of the BDS curriculum as well as to determine whether a five-year system or a four years and one-year internship system was more acceptable. Materials and Methods: A cross-sectional survey was carried out using a self-administered pretested questionnaire on 178 dental undergraduate students of the third and fourth years of the A. B. Shetty Memorial Institute of Dental Sciences, Nitte University, Mangalore, Karnataka, India. The questionnaire comprised of sociodemographic details and 10 questions on the perception and opinion of students toward the change in curriculum. The questionnaire was a close-ended questionnaire. The data was entered into the Microsoft Excel for Windows. Descriptive analysis was carried out for the present study and was presented as a number and percentage. Comparison of the mean scores across genders and year of study was done using the unpaired t test. Results: A total of 178 students participated in the survey. All the students felt that internship was vital to the BDS course and 98% of them wanted to revert back to the four and one-year internship system. The third and fourth year dental students were content with the present four and one-year BDS curriculum and were apprehensive about any changes in the present system. Conclusion: Students considered that one year's internship was vital in the BDS course.